2023
DOI: 10.37989/gumussagbil.1320941
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Forensic Cases Admitted to the Emergency Department: A Retrospective Analysis

Merve AYDIN,
Ceyda UZUN ŞAHİN

Abstract: This study was conducted retrospectively to determine the profile of forensic cases admitted to the emergency department of a university hospital. 127242 patients admitted to the emergency department of a university hospital within one year were retrospectively reviewed in terms of age, gender, type of event, the season of occurrence, age, and gender distribution of the type of event. The data were analyzed using the SPSS 23.0 package program. Out of all the forensic cases analyzed, 35.8% (n: 525) were in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Considering the nature of forensic events, we see that traffic accidents ranked first with 33.3%, followed by assault and battery cases with 24.1% and occupational accidents with 21.5%. In our study, it was found that physicians kept forensic reports mostly related to traffic accidents, which was consistent with similar studies in the literature 2,25,26,29,[31][32][33] . In addition to the fact that traffic accidents and related injuries are still a major problem in our country, it was associated with the fact that our hospital was located close to the city center and intercity road junction.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Considering the nature of forensic events, we see that traffic accidents ranked first with 33.3%, followed by assault and battery cases with 24.1% and occupational accidents with 21.5%. In our study, it was found that physicians kept forensic reports mostly related to traffic accidents, which was consistent with similar studies in the literature 2,25,26,29,[31][32][33] . In addition to the fact that traffic accidents and related injuries are still a major problem in our country, it was associated with the fact that our hospital was located close to the city center and intercity road junction.…”
Section: Resultssupporting
confidence: 92%
“…The mean age was 33.4 years (±15.7) and approximately half of the cases (49.4%) were between 21 and 40 years of age. The high number of forensic cases in this age group, which plays a greater role in the active period of the life process, was found to be consistent with similar studies in the literature [25][26][27][28][29][30] .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation